PENGARUH PERAN KEPALA SEKOLAH DAN IKLIM SEKOLAH TERHADAP MOTIVASI KERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN KALIWUNGU KABUPATEN SEMARANG - Sumarni Sumarni; Ngurah Ayu Nyoman Murniati; Yovitha Yuliejantiningsih (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2020)
The problems in this study are: 1) whether there is an influence of the role of the school principal on teacher work motivation; 2) whether there is an influence of the school climate on teacher work motivation; 3) whether there is an influence on the role of the principal and the school climate on the motivation of the teacher's work.The purpose of this study is to analyze and find out: 1) the influence of the role of the principal on teacher motivation to work; 2) the influence of the school climate on teacher work motivation; 3) the influence of the role of the principal and the school climate on teacher motivation.This type of research is survey research with a quantitative approach. The population in this study were all public elementary school teachers in Kaliwungu District with a total of teachers. The sampling technique used proportionate stratified random sampling, with a sample of teachers. Data collection techniques use interviews and questionnaires. While the data analysis technique uses simple regression analysis and multiple regression analysis.The results of the study concluded that: 1) The role of the principal has a significant effect on the motivation of the work of public elementary school teachers in Kaliwungu District. The influence of the principal's role on teacher work motivation is 17.5% and 82.5% is influenced by other variables outside of the role of the principal; 2) The school climate has a significant effect on the motivation of the work of public elementary school teachers in Kaliwungu District. The influence of the school climate on teacher work motivation is 14.3% and 85.7% is influenced by other variables outside of the school climate; 3) The role of the head as if and the school climate together have a significant effect on the competency of professional SD teachers in Kaliwungu District. The influence of the role of the principal and the school climate together is 21.9%. The role of the principal has a greater influence than the school climate, although the difference is not too far away.Keywords: School Principal's Role, School Climate, Motivation of Teacher's work